Influences of agronomic management on maize grain zinc and iron concentrations: A global assessment - Kihara, Job Maguta; Gudeta, Sileshi W.; Bolo, Peter; Mutambu, Dominic; Kalimuthu, Senthilkumar; Sila, Andrew; Mina, Devkota; Kazuki, Saito (2023)
Zinc application is necessary for increasing both grain Zn and grain Fe. Organic inputs significantly increased grain Zn concentrations relative to the NPK control. Combining soil and foliar application of Zn increased both grain Zn and Fe concentrations. Agronomic biofortification of Zn and Fe in maize can be achieved without yield penalty or protein and Fe concentration dilution. Agronomic practices that build up soil organic matter, maintain soil pH and sustain soil-Zn are encouraged for optimum maize response to zinc applications.